Analysis Of Agricultural Inflation Fluctuation In Indonesia - Widia Wardani (JASc (Journal of Agribusiness Sciences), 2020)
Inflation is an economic disease that cannot be ignored, because it can have a very broad impact. Therefore inflation is often the target of government policy. Inflation is characterized by a general and continuous rise in prices. The sharp surge in the national inflation rate without offset by the nominal income of the people, has caused the people's income to decline. The phenomenon of inflation in Indonesia is actually just a short-term phenomenon and that occurs situationally, but as is common in other developing countries, the problem of inflation in Indonesia is more on the problem of long-term inflation because there are still structural obstacles in country's economy. The development of the agricultural sector in Indonesia is still considered the most important sector of the overall results of economic development. The sharp surge in the national inflation rate without offset by the nominal income of the people, has caused the people's income to decline. Also per capita income of the population fell relatively quickly, which resulted in Indonesia re-entering the poor countries. If you see the tremendous influence of the surge in inflation in Indonesia (as a result of imported inflation triggered by the depreciation of the rupiah in foreign currencies) on the national economy, it is necessary to pay extra attention to this inflation problem. By looking at the factors causing the emergence inflation in Indonesia and what steps should be taken to get out of this inflationtrap.